BIAS GENDER DALAM PENDIDIKAN NON FORMAL (TPA/TQA) TAMAN PENDIDIKAN AL- QUR’AN DI KOTA MAKASSAR - Jamal Mirdad; Ratnah Rahman (SOSIORELIGIUS, 2021)
This paper discusses gender bias in non-formal education in the educational park read the Qur'an Makassar City. The occurrence of gender bias towards nonformal TPA/TQA education in Makassar is caused by several factors, namely: First, the level of education and educational background of teachers or Ustad / Ustadzah who teach in TKA / TPA are still relatively low, Second, stereotypes of girls, Third, is social and cultural and fourth is the understanding of kindergarten /landfill teachers who understand some of the evidence in the Qur'an that men's degrees are higher than women's.